Cultural Tourism Route Development in Takua Pa Old Town, Phang Nga Province - บุญวรรโณ, สกาวรัตน์; Laeheem , Kasetchai; Limpradit, Banthita (Community and Social Development Journal, 2020)
The purpose of this qualitative research was to develop a cultural tourism route in Takua Pa Old Town, Phang Nga Province by collecting data from a focus group discussion of 12 informants, consisting of a community committee, historians and Tourism Related Stakeholders to tourism. Relying on in-depth interview participatory observation, data were analysed, classified, and interpreted. Conclusions were drawn from descriptive analysis. The result of the research shows that Tourism routes in the Takua Pa Old Town area could be classified according to the composition and tour program. Three routes were proposed for further development of tourism management based on the cost of the area, preservation of the community value, and the Tourism Capacity Management the local cultural resource base: 1) the historical route as a full-day program, One Day Tour, 2) the half-day tour of the Authenticity and Uniqueness Route, and 3) the social studies path as a half-day tour program.